A systematic review and meta-analysis of the performance of two point of care typhoid fever tests, Tubex TF and Typhidot, in endemic countries. - Kamala Thriemer; Benedikt Ley; Joris Menten; Jan Jacobs; Jef van den Ende (PLoS ONE)
Background In the absence of well-equipped laboratory infrastructure in many developing countries the accurate diagnosis of typhoid fever is challenging. Rapid diagnostic tests (RDT) with good performance indicators would be helpful to improve clinical management of suspected cases. We performed a systematic literature review and meta- analysis to determine the performance of TUBEX TF and Typhidot for the diagnosis of typhoid fever using PRISMA guidelines. Methods Titles and abstracts were reviewed for relevance. Articles were screened for language, reference method and completeness. Studies were categorized according to control groups used. Meta-analysis was performed only for categories where enough data was available to combine sensitivity and specificity estimates. Sub-analysis was performed for the Typhidot test to determine the influence of indeterminate results on test performance. Results A total of seven studies per test were included. The sensitivity of TUBEX TF ranged between 56% and 95%, Specificity between 72% and 95%. Meta-analysis showed an average sensitivity of 69% (95%CI: 45-85) and an average specificity of 88% (CI95%:83-91). A formal meta-analysis for Typhidot was not possible due to limited data available. Across the extracted studies, sensitivity and specificity estimates ranged from 56% to 84% and 31% to 97% respectively. Conclusion The observed performance does not support the use of either rapid diagnostic test exclusively as the basis for diagnosis and treatment. There is a need to develop an RDT for typhoid fever that has a performance level comparable to malaria RDTs.